Design and Simulation of an Aperture-Coupled Microstrip Patch Antenna for 6 GHz FR1 Band Applications - Santoso, Subekti Ari; Adiwidya, Andre Suwardana; Martini , Ni Putu Devira Ayu; Jantarachote, Vasan (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2026)
Microstrip patch antennas are widely used for 6 GHz FR1 applications, but practical design references in this frequency band are still limited. This study aims to investigate the design and electromagnetic performance of a compact aperture coupled microstrip patch antenna (ACMPA) operating near the 6 GHz FR1 spectrum using full-wave simulations in CST Studio Suite. Two antenna configurations were designed and evaluated using CST Studio Suite on a Rogers RT/duroid® 6002 substrate. The antenna performance was evaluated in terms of reflection coefficient, VSWR, impedance bandwidth, realized gain, and radiation efficiency. The optimized design (D2) achieves an impedance bandwidth of approximately 73 MHz (6.03–6.11 GHz) with VSWR below 2, a realized gain of approximately 7.7 dBi, and radiation efficiency close to 75%. The simulation results indicate that optimizing the coupling-antenna geometry optimization enhances the electromagnetic coupling mechanism, resulting in improved impedance matching, realized gain, and radiation efficiency while preserving a compact single-element antenna structure. These findings confirm that optimizing the aperture geometry in a single-element configuration is an effective design strategy that reduces fabrication complexity to improve the performance of compact ACMPA antennas.